The Magi and the Star in the Gospel of Matthew and Early Christian Tradition - Hegedus, Tim (Laval théologique et philosophique, 2003)
AbstractThe Matthean pericope (2.1-12) of the Magi and the star of Bethlehem prompted a variety of responses among early Christian commentators of the second to the fifth centuries. These responses reflect a range of attitudes among the early Christians towards astrology, which was a fundamental and pervasive aspect of ancient Greco-Roman religion and culture. Some early Christian writers repudiated astrology absolutely, while others sought to grant it some degree of accommodation to Christian beliefs and practices. Interpretations of the Matthean pericope offer an index to the range of such views. This paper examines the motifs of the Magi and of the star in Matthew 2.1-12 as well as a number of early Christian interpretations of the pericope as evidence of a pattern of ambivalence in early Christian attitudes toward Greco-Roman astrology.